Taxonomic novelties and synopsis of the genus digitaria (Poaceae, Panicoideae, Paniceae) in Puerto Rico and the Virgin Islands - Vega, Andrea Susana (2018)
The present paper reports 18 taxa of Digitaria in Puerto Rico and the Virgin Islands as a contribution to an ongoing floristic project. Digitaria filiformis var. dolichophylla, D. fragilis, D. sacchariflora, and D. similis constitute new reports. Digitaria ekmanii, D. fuscescens, D. panicea, and Digitaria × umfolozi are excluded taxa. This contribution includes synonymy, iconography, geographic distribution and habitat, vernacular names, specimens examined and a key for the identification of taxa. Digitaria filiformis var. dolichophylla is fully illustrated for the first time.